PENINGKATAN KAPASITAS ANGGOTA DPRD KABUPATEN CILACAP DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Alizar Isna (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the functions of the DPRD is the legislative function, which includes the preparation and stipulation of Regional Regulations (Raperda) for the Regional Revenue and Expenditure Budget (APBD). In order to increase the capacity of DPRD members in the legislative function, the Cilacap Regency DPRD held training which was packaged in the form of an Academic Study of the 2024 Regional Revenue and Expenditure Budget (APBD) Draft Regional Regulations (Raperda). The training used 2 learning methods, namely varied lectures and hypothetical situation techniques. , one of which discusses the material "Consistency or Conformity Between Planning Documents and Between Planning Documents and Budgeting". This material is discussed from a theoretical perspective and relevant laws and regulations. At the end of the material presentation, it ended by discussing the suitability of the development focus of Permendagri No. 15 of 2023 with RKPD 2024 and KUA 2024 as well as the suitability of the development focus of Permendagri No. 15 of 2023 with RKPD 2024 and KUA 2024. The discussion process is assisted by work tables which will make it easier for training participants to discuss the theme of suitability of aspects in regional planning and budgeting.